2000
DOI: 10.1093/oxfordjournals.aje.a010241
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry in Relation to Prostate Cancer Risk in the Netherlands Cohort Study

Abstract: In the Netherlands Cohort Study, the authors investigated whether anthropometry is associated with prostate cancer risk. At baseline in 1986, 58,279 men aged 55-69 years completed a self-administered questionnaire on diet, anthropometry, and other risk factors for cancer. After 6.3 years of follow-up, 681 cases were available with complete data on height and weight at baseline, and for 523 cases, there were data for weight at age 20 years. In both age-adjusted and multivariate case-cohort analyses (adjusted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 44 publications
14
131
1
4
Order By: Relevance
“…Our observation for an association between obesity or height and prostate volume are consistent with several studies evaluating prostate size or clinical BPH. 4,6,9,11 For example, Freedland et al 9 reported prostate weight was about 5 g greater among prostate cancer patients (70.2%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation for an association between obesity or height and prostate volume are consistent with several studies evaluating prostate size or clinical BPH. 4,6,9,11 For example, Freedland et al 9 reported prostate weight was about 5 g greater among prostate cancer patients (70.2%…”
Section: Discussionmentioning
confidence: 99%
“…9 However, BMI was not associated with prostate volume in the Baltimore Longitudinal Study of Aging. 10 Although visceral adiposity 4,6 and height 11 have been associated with clinical BPH, little is known about their relationships with prostate volume.…”
Section: Introductionmentioning
confidence: 99%
“…1 The relationship of obesity to prostate cancer risk is controversial, with some studies indicating that obesity is associated with a decreased incidence of prostate cancer 2 and other studies suggesting an increased incidence of prostate cancer [3][4][5] and worse prostate cancer survival among obese men. [3][4][5] Two recent, retrospective, multi-institutional studies have reported greater recurrence rates among obese patients after radical prostatectomy (RP). 6,7 Obesity was an independent predictor of recurrence in one but not in the other.…”
Section: Authorsmentioning
confidence: 99%
“…Finally, Wright et al found that weight gain from the age of 18 years significantly increased the risk of fatal, but not incident, prostate cancer (Wright et al, 2007). However, not all studies have found an association (Schuurman et al, 2000;Song et al, 2008).…”
Section: Prostate Cancermentioning
confidence: 99%